The Food We Eat, the Stories We Tell : Contemporary Appalachian Tables - Gipe, Robert; Wallace, Emily; Croley, Michael; Balestier, Courtney; Clapsaddle, Annette Saunooke; Huggins, Abigail; Margolies, Daniel S., 1969-; Brown, Karida, 1982-; Locklear, Erica Abrams; Smith, Lora E., 1979-; Smith, Lora E., 1979-; Engelhardt, Elizabeth S. D. (Elizabeth Sanders Delwiche), 1969- (Book collections on Project MUSE., 2019)
"Blue Ridge tacos, kimchi with soup beans and cornbread, family stories hiding in cookbook marginalia, African American mountain gardens-this wide-ranging anthology considers all these and more. Diverse contributors show us that contemporary Appalachian tables and the stories they hold offer new ways into understanding past, present, and future American food practices. The poets, scholars, fiction writers, journalists, and food professionals in these pages show us that what we eat gives a beautifully full picture of Appalachia, where it's been, and where it's going"--